Strengthening neonatal care in a district hospital of Nepal: experience from scholarship bonding - Twanabasu, Sajal (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Neonatal mortality remains a major contributor to under-five deaths in Nepal. A large proportion of neonatal deaths can be prevented by improving the quality of care for small and sick newborns (SSNBs). The objective of this manuscript is to share the experience of improving neonatal care at Dhading Hospital during a government postgraduate (PG) scholarship bonding period.Intervention: Interventions included staff capacity building through a special newborn care unit (SNCU) orientation package, allocating dedicated nurses to the SNCU, strengthening referral pathways, integrating Infant and Family Centered Developmental Care (IFCDC), optimizing infection prevention and infrastructure, and ensuring robust data collection and reporting.Outcomes: Referral rates decreased as SNCU care improved. Staff confidence in managing critically ill neonates increased. IFCDC practices were successfully integrated, infection prevention measures improved, and data reporting into the district health information system (DHIS 2) was established.Conclusion: Scholarship bonding can significantly help bridge gaps in neonatal care. Even within resource-limited district hospitals, simple systemstrengthening interventions can lead to meaningful improvements in neonatal survival.